2009
DOI: 10.1007/s10460-009-9204-y
|View full text |Cite
|
Sign up to set email alerts
|

Linking future population food requirements for health with local production in Waterloo Region, Canada

Abstract: Regional planning for improved agricultural capacity to supply produce, legumes, and whole grains has the potential to improve population health as well as the local food economy. This case study of Waterloo Region (WR), Canada, had two objectives. First, we estimate the quantity of locally grown vegetables, fruits, legumes, and whole grains needed to help meet the Region of Waterloo population's optimal nutritional requirements currently and in 2026. Secondly, we estimate how much of these healthy food requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 12 publications
(8 reference statements)
0
29
0
1
Order By: Relevance
“…Researchers looking at the Willamette Valley in Oregon found that in 2008 agriculture production met only 10% of the recommended vegetable servings and 24% of the recommended fruit servings for the valley's population (Giombolini, Chambers, Schlegel, & Dunne, in press). Desjardins, MacRae, and Schumilas (2010) looked at the Waterloo region of Ontario, Canada, and found it would be feasible to supply 10% to 50% of the additional intake needed to meet nutritional guidelines of particular fruit and vegetable crops that grow well in the area. However, there remains a dearth of research relating an urban land base to food consumption by urban residents.…”
Section: Urban Agriculture and Sustainable Urbanizationmentioning
confidence: 99%
“…Researchers looking at the Willamette Valley in Oregon found that in 2008 agriculture production met only 10% of the recommended vegetable servings and 24% of the recommended fruit servings for the valley's population (Giombolini, Chambers, Schlegel, & Dunne, in press). Desjardins, MacRae, and Schumilas (2010) looked at the Waterloo region of Ontario, Canada, and found it would be feasible to supply 10% to 50% of the additional intake needed to meet nutritional guidelines of particular fruit and vegetable crops that grow well in the area. However, there remains a dearth of research relating an urban land base to food consumption by urban residents.…”
Section: Urban Agriculture and Sustainable Urbanizationmentioning
confidence: 99%
“…The findings of earlier food systems studies have helped shape our understanding of the environmental impact and land use of different agricultural systems and diets (for example see Peters et al 2007;Peters et al 2008b) as well as highlighting the potential of local agricultural production to meet nutritional needs of communities (Herrin and Gussow 1989;Feenstra 2002;Peters et al 2003;Desjardins et al 2010) and subsequently the benefits to local economies (Feenstra 2002;Desjardins et al 2010). Additionally the results of foodshed analyses has highlighted the potential for regional agricultural policy and planning to influence production and play an important role in community health (Peters et al 2003;Rosenberg et al 2006;Desjardins et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing recognition by agriculturalists and the broader society, reinforced by many market signals, of the emerging potential in the re-localization of food systems (Brinkley, 2012;Desjardins et al, 2010;Palan, 2005;Peters, Wilkins & Flick, 2006;Pothukuchi & Kaufman, 1999). However, the hegemony of the contemporary agri-food production and marketing system (Heffernan, 2005) and our economic environment in general has thus far precluded the substantial emergence of this sector.…”
Section: Resultsmentioning
confidence: 99%